PENGARUH KEBIJAKAN HUTANG DAN DIVIDEN TERHADAP NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE - FATMAWATI SOLICHAH (STIE Indonesia Malang, 2017)
The purpose of this research is to find out and analyze; 1) partially influence policy dividendpolicy and debt against the value of property and real estate companies listed on theIndonesia stock exchange, 2) influence of simultaneous policy dividend policy and debtagainst the value of property and real estate companies listed on the Indonesia stockexchange, 3) influence is dominant among policy variables policy dividend and debt againstthe value of property and real estate companies listed on the Indonesia stock exchange. Thisresearch type is explanatory research, while the Population of the research was the real estateand property companies listed on the Indonesia stock exchange (idx) of the period 2012-2014, with a purposive sampling method. Based on the results of the analysis of researcheither in descriptive nor inferensial can be summed up as follows: 1) dividend policy and debtpolicy effect of partial and significantly to the value of the company's property and real estatein Indonesia stock exchange period in 2012-2014, 2) dividend policy and debt policy takeeffect simultaneously and significantly to the value of the company's property and real estatein Indonesia stock exchange period in 2012-2014 , as well as 3) influential dividend policy ofthe dominant against the value of the company's property and real estate in Indonesia stockexchange period in 2012-2014.Keywords: debt policy, policy dividends and the value of the company